Financial stock application using websocket in real time application - Chika Ogochukwu Yinka-Banjo; Ogundeyi Kehinde Esther (Institute of Advanced Engineering and Science, 2019)
Real time web application involves clients which is also known as a browser getting updates from the server as they happen. The finance world is moving fast, and human brains cannot sustain processing data at that speed, so algorithms are used with regards to the limit observed in old-style real-time communication which include long polling, polling server-sent events and comets, this paper uses WebSocket technology when dealing with real time applications. The Web Socket offers improved result as compared to the conventional approaches that are considered to be good solution of providing real time information and lessens overhead acquired while communicating over the internet and offers stateful, efficient communication among web servers and clients. When there is need to track companies worth/stock using a dashboard immediately and not some seconds ago, WebSocket can be used to stream data without delays.